Using augmented reality application toward university students to improve pronunciation on vowel sounds - Rizal Fadli (Jujurnal Publisher, 2024)
In teaching and learning English speaking, there are many English as foreign language (EFL) undergraduates who find some difficulties in learning English pronunciation. One of the challenges that undergraduate students finds in learning activity is the pronunciation mastery in Universities Muhammadiyah Yogyakarta was still low because English is not their native language and monotonous teaching media. The researcher adopted Augmented Reality (AR) application as the media to learning English pronunciation. This thesis is written 1) How is the pronunciation mastery of the students in the control group, 2) How is the pronunciation mastery of the students in the experimental group, 3). Is there any significant difference of the students’ pronunciation mastery in Control Group and Experimental group of the undergraduate students of English Department on the Second semester at Universitas Muhammadiyah Yogyakarta in the academic year of 2022/2023. The present study adopts qualitative approach where the method used in this research was a quasi- experimental design, pre-post test, and control- experiment group. Total sample is 20 students university and using a convenience sampling technique, the data collected through a recorded oral test. The data will be analyzed and calculated using PRAAT software and SPSS version 25. The research findings prove that AR application may improve the students‟ production of vowel sounds. After using AR application as media learning pronunciation, there was a significant difference only in back vowel sounds. It can be concluded that there was a significant effect of AR application in improving students‟ pronunciation of vowel sounds. The results of this study are expected to encourage other researchers to conduct research related to the development, innovation, and use of AR application, especially in English education.